Liberalisasi ekonomi, pemerataan, dan kemiskinan - Habibie, B. J. (Bacharuddin Jusuf), 1936-2019.; Soetrisno, Loekman; Umaya, Faraz; Universitas Gadjah Mada. Pusat Penelitian Pembangunan Pedesaan dan Kawasan (Yogyakarta : Diterbitkan atas kerjasama dengan Pusat Penelitian Pembangunan Pedesaan dan Kawasan (P3PK), Universitas Gadjah Mada dan Penerbit PT. Tiara Wacana Yogya, 1995)
Economic conditions in Indonesia; development of rural areas, improving quality of cottage industries, small business, home-based business in the wake of international trade; papers of a seminar.
Includes bibliographical references and index.
Keywords: Rural development -- Indonesia; Indonesia -- Social conditions; Indonesia -- Economic conditions -- 1945-1966.